Gender differences in lipid goal attainment among Chinese patients with coronary heart disease: insights from the DYSlipidemia International Study of China. (21st March 2015) - Yu, Bilian; Zhao, Shuiping; Hu, Dayi; Ambegaonakr, Baishaili M.; Jia Er, Bu Ai; Guiwen, Cao; Buxing, Chen; Hong, Chen; Jin, Chen; Jing, Chen; Liefeng, Chen; et al.
Abstract: Despite great advances in lipid-lowering therapy, the gender-based disparities in lipid goal success among Chinese coronary heart disease (CHD) patients receiving lipid-lowering treatment remained uncharacterized. Furthermore, little is known about potential causes for this gender imbalance. This cross-sectional trial included 25 697 patients treated with lipid-lowering agents from 122 centres between April 2012 and October 2012; data for 9420 participants with CHD were analysed in the present study; all underwent clinical examination and had their latest fasting lipid profiles while on lipid-lowering therapy recorded. Logistic regression was used to explore possible factors associated with gender disparity in goal attainment rates, and to what extent each factor contributes. Of 9420 CHD patients (42.5% women) evaluated, women had a significantly lower overall low-density lipoprotein cholesterol (LDL-C) success rate than men (46.2 vs. 62.7%, P < 0.0001). Among CHD patients with diabetes, only 31.5% of women and 46.4% of men ( P < 0.0001) attained the optional LDL-C target of <80 mg/dL. More than half (54.0%) of female patients failed to attain their non-high-density lipoprotein cholesterol (HDL-C) goal. Approximately 7.5, 8.8, 7.5, and 6.8% of gender disparity in LDL-C goal attainment rate was attributable to the gender difference in use of an anti-diabetic, anti-hypertensive, anti-platelet treatment, and the dosage of statin treatment, respectively. Although great improvements have been made over the past decade, there is still a preventive gap in high-risk and very high-risk CHD patients regarding LDL-C and non-HDL-C levels and that this gap is apparently greater in women.